“YOU’RE EITHER WITH US OR AGAINST US”: POSTCOLONIALITY, SPECTATORSHIP AND THE MILLENNIAL HOLLYWOOD CINEMA - Robin Xavier (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Hollywood has a special knack for genre films. The historical thrillers of the recent times, unlike those of the past, put the third world in an Orientalist imagination, as a problematic location where the evil is dancing. The cases in target are historical rescue dramas – Argo (2012) and Captain Phillips (2013). Both are texts, among many other movies, which represent the paranoid fear of the third world that exists in the imperialist American(ized) psyche. As Stam and Spence note, the texts produce “aberrant readings” in the third world spectator/s. The paper attempts to problematize the concept of spectatorship by challenging the theories of representation. The theories of spectator positioning, by Metz and Mulvey, ignore or at least do not consider the flesh and blood of the living spectator. Thus, the ideal(ized) spectator is a myth, and s/he is rooted in a historical continuum and material present so that the readings are all influenced by co-texts from the rest of the world – cinematic as well as non-cinematic. The exemplars analyzed in the paper are the videotapes by IS which produce a counter-aberrant reading in the spectators. The films are contested from the viewpoint of Neoimperial and counterimperial discourses in which how historical narratives are often viewed through the lens of contemporary ideology, reinforcing the cultural hegemony of dominant groups. The paper also attempts to redefine the concept of empire from a Neoimperialist perspective and contests the monolithic understanding of postcolonialism based on presentism.